Association of meaning in life with preventive healthcare use among Chinese adults: are there age and gender differences? - Dexing Zhang; Zijun Xu; Zuyao Yang; Weiju Zhou; Peter Man-hin Cheung; Eric Kam-pui Lee; Baoliang Zhong; Dong Xu; Xue Li; Yaojie Xie; Gao Yang; Shuiyuan Xiao; et al. (BMC, 2022)
Abstract Background Meaning in life could be of clinical importance in stimulating healthy and preventive behaviors. The study aimed to investigate the association between meaning in life and preventive healthcare use among Chinese adults, and to assess their age and gender differences in the association. Methods A cross-sectional online survey was conducted among 1444 adults aged 18-64 years in February 2020 in China. Logistic regression models were employed to examine the association of meaning in life with preventive health checkups and assess their age and gender differences. Results The mean score of meaning in life was 5.801 (Standard Deviation = 1.349) out of 7. Each unit increase on the level of meaning in life was associated with 12.2% higher likelihood of using preventive health checkups (any type) (adjusted odds ratio 1.122, 95% confidence interval 1.015-1.241) after adjustment for sociodemographic factors, comorbidity and other psychological health factors. Meaning in life was significantly associated with the uses of X-ray (1.125, 1.010-1.253), B-ultrasound (1.176, 1.058-1.306), and blood testing (1.152, 1.042-1.274). The associations between meaning in life and these types of preventive healthcare increased with age, but there were no gender differences in these associations. Conclusion Higher meaning in life was independently related to more preventive health checkups. Strategies to strengthen health education and interventions to improve experience of meaning in life might be an important component to increase preventive healthcare use in China.